Synthesis Of Titanium DioxideZeolite Catalyst And Treatment Of Sulfamethoxazole - Tan, Ling Chi (Universiti Sains Malaysia, 2022)
The presence of SMX, that is stable and mobile in soils and is regularly detected in various aquatic compartments. The breakdown of these contaminants is poor in wastewater treatment plants. The development of effective SMX removal strategies is essential. Heterogeneous photocatalysis is one of the AOP that is thought to have the most promise for treating SMX while functioning at room temperature and pressure. As photocatalysis chemical reactions are complex, the composite catalyst could improve photocatalysis. TiO2/Zeolite is proposed for the degradation of SMX because of the good performance of composites in the photodegradation of propane based on previous study. In this study, SEM, XRD, UV-VIS spectroscopy, FTIR, and BET were used in catalyst characterization. The nanocomposite was used in photocatalysis to degrade SMX under simulated solar irradiation. The operating factor including the catalyst dosage, was compared with previous studies to obtain the optimum conditions required for the maximum degradation rate. The irradiation time for optimum conditions outlined the removal efficiency of SMX by using TiO2/Zeolite with light, without light and zeolite (for the control run) as catalyst. Characterization results showed that application of TiO2 to zeolite stabilised anatase phase of TiO2, enhanced both surface area and the pore volume of the TiO2/zeolite material. The optimum catalyst dosage is 0.20g with the initial concentration of SMX being 20mg/L with 14.67% of removal efficiency. The 6 hours of irradiation time by using TiO2/Zeolite with light had shown that it's an effective way to break down SMX under optimum condition.